Developing products in half the time - Smith, Preston G. (Van Nostrand Reinhold, 1991)
Developing Products in Half the Time is a classic on the art and science of competitive product development. This is a real manager's book, one that takes a sophisticated view of project dynamics, corporate structures, and the people who ultimately make projects succeed. Each of its 16 chapters is a self-contained examination of a single aspect or stage of the development process, and the whole adds up to a rational and well-considered approach transferable to real-world situations. Featured topics include the definition of rational product objectives, the creation of economic models for a new product, the management of a project's "fuzzy" early stages, staffing and motivational issues, organization and project management, the relationship between design and manufacturing, and risk management.